New Method for Determination of Trans-resveratrol for Quality Evaluation of Red Wines by Multivariate Calibration Associated with UVVIS Spectroscopy - Mota, Milleno D.; Meira, Marilena; David, Juceni P.; de Oliveira Ribeiro, Erika M.; Brandão, Hugo N.; do Vale, Ademir E.; David, Jorge M. (Current Analytical Chemistry, 2021)
Background: This work describes a fast, simple, sensitive, and low-cost method for the identification of resveratrol in different brands and varieties of red wines. Methods: It was developed based on a comparison of the UV-VIS spectra of the samples and samples enriched with different concentrations of the trans-resveratrol standard. The spectra were analyzed by chemometric principal component analysis (PCA) and multivariate calibration. Results: The PCA data indicated that only 4 main components made possible group samples based on the grape variety characteristics and/or production region. Conclusion: From the construction of partial least squares (PLS) and multiple linear regression (RLM) models, it was possible to predict the sample trans-resveratrol content with that sample showing similarities between the groups observed in the PCA and the samples used in the model constructions. The predicted trans-resveratrol present in these samples ranged from 0.29 to 23.3 mg L-1. This multivariate method suggested a good predictive capacity of determination of resveratrol concentrations in commercial red wines.
Keywords: Multivariate methods